2020
DOI: 10.1080/02656736.2020.1750712
|View full text |Cite
|
Sign up to set email alerts
|

US-guided laser treatment of parathyroid adenomas

Abstract: Objective: To determine the clinical efficacy of laser ablation for the tredatment of primary hyperparathyroidism (pHPT). Materials and methods: Twelve patients with pHPT were treated with laser ablation. Energy was administered by means of 1.5 m optical fibers percutaneously placed into the target via 21 G needles. A laser ablation unit (EchoLaser X4, Esaote) applied 3 W power for 400-600 s/fiber/insertion to a total 3600-9000 Joules of energy. Patient serum parathyroid hormone (PTH) and calcium levels were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In recent years, US-guided thermal ablation for pHPT has been demonstrated to be a promising option because of its minimal invasiveness, safety, promising efficacy, wide indications, and rapid postoperative recovery [8][9][10][11][12]. However, the cure rate of MWA is approximately 82.1-89.4%, and still there are some patients have failed procedures [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, US-guided thermal ablation for pHPT has been demonstrated to be a promising option because of its minimal invasiveness, safety, promising efficacy, wide indications, and rapid postoperative recovery [8][9][10][11][12]. However, the cure rate of MWA is approximately 82.1-89.4%, and still there are some patients have failed procedures [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is recommended as the definitive curative treatment for pHPT [5][6][7]. In recent years, after more than a decade of clinical application, ultrasound-guided thermal ablation has been demonstrated to be effective in inactivating parathyroid nodules and normalizing serum PTH and calcium levels [8][9][10][11][12]. A recent prospective study showed that microwave ablation (MWA) and surgical resection provided comparable results in terms of cure rate in the treatment of pHPT [10].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most minimally invasive techniques for the removal of in situ tumors, ultrasound-guided percutaneous laser ablation (PLA) has been clinically applied for the treatment of various benign and malignant tumors [12][13][14][15]. Similar to ultrasound-guided radiofrequency ablation (RFA) and microwave ablation (MWA), PLA can generate a high temperature locally through energy, which leads to tissue thermal denaturation and coagulative necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal ablations have been used to treat primary hyperparathyroidism for a decade, including high-intensity focused ultrasound (HIFU) ( 9 , 11 ), laser ablation (LA) ( 10 , 12 , 17 ), radiofrequency ablation (RFA) ( 14 , 18 ) and MWA ( 13 , 15 , 19 , 21 ). Although their mechanisms to produce heat vary a lot, thermal ablation techniques produce heat to ablate lesions through a mechanism of tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%